2014
DOI: 10.1111/jvim.12478
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Findings and Survival in 56 Sick Neonatal New World Camelids

Abstract: BackgroundInformation pertaining to clinical presentation and outcome of neonatal New World camelids (NWC) is limited when compared to calves and foals.HypothesisValues of variables at admission and subsequent treatment would predict survival in sick neonatal NWC.AnimalsFifty‐six client‐owned sick neonatal NWC presented over a 10‐year period to the Purdue University Veterinary Teaching Hospital.MethodsA retrospective study was performed. Inclusion criteria were NWC less than 30 days of age with complete medica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 41 publications
1
14
1
1
Order By: Relevance
“…The clinical manifestation of the inflammatory response, SIRS, occurs in response to an infectious or noninfectious assault on the animal (eg, sepsis, burns, trauma), and it is considered to be present if 2 or more of the following occur: tachycardia, tachypnea (or respiratory alkalosis), hypothermia or hyperthermia, leukocytosis or leukopenia and neutrophilic left shift. A diagnosis of sepsis includes the presence of SIRS and the identification of infection . In our study, most cases met at least 2 SIRS criteria at admission as well as yielding positive bacterial cultures.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…The clinical manifestation of the inflammatory response, SIRS, occurs in response to an infectious or noninfectious assault on the animal (eg, sepsis, burns, trauma), and it is considered to be present if 2 or more of the following occur: tachycardia, tachypnea (or respiratory alkalosis), hypothermia or hyperthermia, leukocytosis or leukopenia and neutrophilic left shift. A diagnosis of sepsis includes the presence of SIRS and the identification of infection . In our study, most cases met at least 2 SIRS criteria at admission as well as yielding positive bacterial cultures.…”
Section: Discussionmentioning
confidence: 68%
“…The diagnosis of SIRS was made based on the presence of 2 or more of the following abnormalities: temperature >39°C or <36°C, heart rate >120/min, respiratory rate >40/min, WBC count >12 × 10 3 /μL or <6 × 10 3 /μL or >10% band neutrophils, and hyperlactatemia >2 mmol/L. The diagnosis of sepsis was made if SIRS was present and if bacterial infection was confirmed by microbial culture …”
Section: Methodsmentioning
confidence: 99%
“…9 Choanal atresia has been associated with a low survival rate in New World camelids. 10 Because these species are primarily nasal breathers, affected juvenile animals are unable to breathe while suckling, which typically results in fatal aspiration pneumonia.…”
Section: Discussionmentioning
confidence: 99%
“…Reports of successful treatment of choanal atresia in camelids are sparse, 17,18 likely because of the poor outcomes after the procedure and the ethical issues related to treatment of a potentially heritable disease. 10 Approaches that have been used for treatment of choanal atresia in domestic animal species include transnasal puncture with fluoroscopic guidance, 17,18 nasal flaps, 19 and transnasal laser ablation techniques. 20,21 In people, transpalatal and transnasal approaches are described, 22 with the transnasal endoscopic approach being the most widely accepted repair technique because of its lesser invasiveness and lower complication rates.…”
Section: Discussionmentioning
confidence: 99%
“…A recent paper found that 155 of 1,065 foals (14.5%) presenting to a referral hospital at less than 14 days of age were diagnosed with NE . The condition was also recognized in 2 of 65 (3.5%) camelid neonates that were presented to a referral hospital at less than 30 days of age . Given that over 33 million calves are born in the United States annually, recognition of NE and identification of risk factors for development of disease and nonsurvival are important.…”
mentioning
confidence: 99%